Exploring community healthcare providers' perceptions on antimicrobial resistance. (September 2019) - Ellen, Moriah E.; Shach, Ruth; Perlman, Saritte
Highlights: Community healthcare practitioners expressed perceptions on antimicrobial resistance (AMR). Participants reflected on causes of and barriers and facilitators to addressing AMR. Factors for these were found at the patient, provider and system levels. Nurses more frequently mentioned patient causes and education compared with physicians. Abstract: Objectives: Antimicrobial resistance (AMR) is a threat to global health, making previously curable diseases disabling or incurable. Human misuse of antimicrobials exacerbates the issue. As stewards to the public and prescribers of antimicrobials, healthcare providers are vital to reducing AMR, thus their perceptions and experiences around the issue must be explored. This study aimed to understand the perceptions of community nurses and physicians regarding the causes of AMR as well as barriers and facilitators to addressing it. Methods: In-depth, semi-structured interviews were conducted to understand the perceptions of nurses and physicians on these issues. Results: Overall, participants expressed that both environmental and human causes at various levels contribute to AMR. Whilst most themes were discussed by both healthcare practitioner groups, nurses more frequently mentioned patient causes and patient education compared with physicians. Participants also reflected on facilitators to reduce AMR, including guidelines, patient and provider education, and top-down and bottom-up initiatives. Identified barriers included patient demands, physician pressures and fears, and systemic overworking of physicians. Conclusion: This study demonstrated numerous factors underpinning AMR and many barriers to addressing it, hence a multifaceted approach is required. This work also offers insight on how different groups can be utilised or will react to interventions.